Method for forming iron nitride coating on surface of substrate of iron or iron alloy

The iron nitride coating part is formed on the surface of the iron or ferroalloy substrate at low temperature by electrochemical nitriding method, which solves the problems of high temperature and long-term environmental safety of the existing nitriding technology, and achieves high efficiency resistance suitable for a variety of industrial applications Corrosion coating.

CN119487240APending Publication Date: 2025-02-18FRENI BREMBO SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041632.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-27
Filing Date
2023-04-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing nitriding technology requires high temperature and long-term treatment of iron or ferroalloy substrates, and has environmental and safety problems, making it difficult to apply to large or thin parts, especially parts that cannot be heated.

Method used

Using electrochemical nitriding method, in an electrolytic bath of an ionic liquid containing nitrogen ions, an iron or ferroalloy substrate is electrochemically nitrided as an anode, and formed at a low temperature (no more than 250°C) through a constant current or constant potential step. Iron nitride coating section.

Benefits of technology

It realizes the rapid formation of a uniform iron nitride coating portion at low temperatures, is suitable for parts that cannot be heated, and is suitable for industrial-scale applications, improving corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005143193170000011
    Figure HDA0005143193170000011
  • Figure HDA0005143193170000012
    Figure HDA0005143193170000012
Patent Text Reader

Abstract

The invention relates to a method for forming an iron nitride coating on the surface of a substrate of iron or iron alloy, comprising the following steps: a) immersing the substrate of iron or iron alloy in an electrolytic bath comprising an ionic liquid in the presence of a counter electrode acting as a cathode, the ionic liquid comprises nitrogen cations and / or nitrogen anions, and the base material is used as an anode; b) subjecting said substrate to an electrochemical nitriding process comprising at least one of the following steps:-a constant current step in which an anode current representative of a predetermined reference current density is applied between the substrate and the counter electrode until a predetermined threshold voltage is reached, at which the anode current is applied between the substrate and the counter electrode until the predetermined threshold voltage is reached; generating an iron nitride coated portion having a predetermined thickness on the substrate; -a constant potential step in which a voltage having a value equal to a predetermined reference voltage is applied between the substrate and the counter electrode until a threshold anode current representing a predetermined threshold current density is reached, at which an iron nitride coating having a predetermined thickness is generated on the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for forming an iron nitride coating on the surface of an iron or iron alloy substrate, and an article comprising an iron or iron alloy substrate and a surface coating of the substrate obtainable by the method. Background Art

[0002] Nitriding is a known surface treatment which is applied to ferrous substrates or ferrous alloys, such as steel or cast iron, to increase their surface hardness and corrosion resistance.

[0003] Currently, nitriding of iron substrates or iron alloys is performed using the following techniques: a) plasma assisted deposition; b) ion beam deposition; c) laser melting; d) vapor deposition; e) cyanide-containing baths.

[0004] However, these nitridation techniques require: high processing temperature, usually between 400°C and 1000°C; long process time, up to hundreds of hours; complex system (e.g., vacuum system and high temperature chamber). In addition, these nitridation techniques have significant environmental and safety issues, such as environmental and safety issues caused by the use of highly toxic cyanide baths.

[0005] Therefore, conventional nitriding techniques are not suitable for most industrial applications. In particular, it is almost impossible to process large parts or components, as well as thin parts or components, by these techniques, because these parts or components are easily affected by thermal deformation.

[0006] The limitations on process temperature imposed by conventional nitriding techniques are particularly problematic. In fact, these techniques are not applicable to parts or components that cannot be heated without losing some of their geometrical properties (eg flatness or roughness).

[0007] The problem underlying the present invention is therefore to provide a method for forming an iron nitride coating on the surface of an iron or iron alloy substrate, such as steel or cast iron, which method can be carried out at temperatures much lower than those required by conventional techniques, in particular at temperatures not exceeding 250° C., and which method can be easily applied on an industrial scale. Summary of the invention

[0008] The above mentioned problem is solved by a method for forming an iron nitride coating on the surface of a substrate of iron or an iron alloy and an article comprising a coating obtainable by said method as outlined in the appended claims, the definitions of which form an integral part of the present description.

[0009] A first object of the present invention is a method for forming an iron nitride coating on a surface of a substrate of iron or an iron alloy, the method comprising the following steps:

[0010] a) immersing the substrate of iron or iron alloy in an electrolytic bath comprising an ionic liquid comprising nitrogen cations and / or nitrogen anions in the presence of a counter electrode acting as cathode, the substrate acting as anode;

[0011] b) subjecting the substrate to an electrochemical nitriding process, wherein the electrochemical nitriding process comprises at least one of the following steps:

[0012] a galvanostatic step in which an anodic current representing a predetermined reference current density is applied between the substrate and the counter electrode until a predetermined threshold voltage is reached at which an iron nitride coating having a predetermined thickness is produced on the substrate;

[0013] - a potentiostatic step in which a voltage having a value equal to a predetermined reference voltage is applied between the substrate and the counter electrode until a threshold anodic current representing a predetermined threshold current density is reached, at which threshold anodic current an iron nitride coating having a predetermined thickness is produced on the substrate.

[0014] A second object of the present invention is an article comprising a substrate of iron or an iron alloy and an iron nitride surface coating on said substrate, wherein said surface coating is obtainable by a method according to the above.

[0015] The method of the invention allows the formation of an iron nitride coating at a much lower temperature than known methods, even at room temperature, and allows a uniform coating to be obtained without changing the morphology and dimensions of the substrate. The method of the invention is therefore particularly suitable for producing surface coatings of substrates that cannot be heated without losing geometrical features such as flatness and roughness.

[0016] Furthermore, the method of the present invention allows the iron nitride coating portion to be formed in a short time of several tens of minutes and is therefore particularly suitable for industrial-scale application.

[0017] In view of the above advantages, the method of the present invention can therefore be applied to any technical field, from precision machinery to the aerospace industry, from the medical field to dental implantology, and even to the automotive field.

[0018] Other characteristics and advantages of the invention will become apparent from the following description of some embodiments given by way of non-limiting indication. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A comparison of the Raman spectrum of a coating of a cast iron sample obtained by the method of the present invention (spectrum A) and the Raman spectrum of a coating of the same sample obtained by a conventional ferrite nitrocarburizing process or FNC (spectrum B) is shown.

[0020] Figure 2 Shown are glow discharge optical emission spectroscopy (GD-OES) spectra obtained for a cast iron sample coated by the method of the present invention and the same cast iron sample without a coating. DETAILED DESCRIPTION

[0021] The present invention relates to a method for forming an iron nitride coating on the surface of an iron or iron alloy substrate, the method comprising: a step a), in which the substrate is immersed in an electrolytic bath containing an ionic liquid including nitrogen ions in the presence of a counter electrode; and a subsequent step b), in which an electrochemical nitridation process of the substrate is started, the electrochemical nitridation process comprising a constant current step and / or a constant potential step.

[0022] Surprisingly, it was found that during the electrochemical nitriding process, nitrogen ions in the ionic liquid contained in the electrolytic bath decompose to produce nitrogen species which diffuse into the substrate of iron or iron alloy to produce a surface coating of iron nitride. Surprisingly, it was observed that in the method according to the invention, there is a surface conversion of the substrate rather than deposition of the coating, thereby avoiding adhesion problems between the substrate and the coating.

[0023] The term "ionic liquid" refers to a chemical compound composed of ions (salts) that is in a liquid state under specific conditions of temperature and pressure. An ionic liquid can be equivalent to a molten salt in all respects and, as a rule of thumb, has a melting temperature below 100°C, so that the ionic liquid is in a liquid state at low temperatures or at room temperature. In the latter case, the ionic liquid is called a room temperature ionic liquid (or RTIL).

[0024] In one embodiment of the present invention, the ionic liquid contained in the electrolytic bath is a room temperature ionic liquid (RTIL).

[0025] The upper temperature limit at which the electrochemical process can be performed is defined by the thermal stability of the ionic liquid.Thus, the electrochemical nitridation process is advantageously performed at a temperature not higher than the thermal degradation temperature of the ionic liquid.

[0026] Preferably, the electrochemical nitridation process is performed at a temperature below 250° C., more preferably, the electrochemical nitridation process is performed at a temperature below 200° C. Even more preferably, the electrochemical nitridation process is performed at room temperature. The term “room temperature” refers to a temperature between about 20° C. and 30° C., such as a temperature between about 20° C. and 25° C.

[0027] Advantageously, both step a) and step b) of the method of the invention are performed at the abovementioned temperature.

[0028] Advantageously, the electrolytic bath in which the substrate is immersed during step a) is at a temperature below 250°C, preferably, the electrolytic bath in which the substrate is immersed during step a) is at a temperature below 200°C, more preferably, the electrolytic bath in which the substrate is immersed during step a) is at room temperature.

[0029] Advantageously, the electrochemical nitridation process of step b) is performed at a temperature below 250°C, preferably, the electrochemical nitridation process of step b) is performed at a temperature below 200°C, and more preferably, the electrochemical nitridation process of step b) is performed at room temperature.

[0030] The fact of adopting a temperature below 250° C. advantageously allows obtaining an iron nitride coating (preferably Fe 200) having a lower crystallinity than that obtained by conventional nitriding techniques, such as plasma techniques, besides allowing a simplification of the operational management of the process. 2-3 N, Fe3N). According to one embodiment, the method of the invention allows obtaining Fe 2-3 A mixture of N (HCP structure, compact hexagonal) and Fe3N (rhombic structure).

[0031] Surprisingly, it was observed that the iron nitride coating obtained by the method of the present invention has a higher corrosion resistance than the iron nitride coating obtained by conventional techniques. Without being bound by theory, it is believed that the lower crystallinity of the iron nitride leads to a reduced extension of the grain edges and thus a reduction in the reactive sites where oxidation processes may occur.

[0032] According to different embodiments, the electrochemical nitridation process comprises a constant current step or a constant potential step, or both a constant current step and a constant potential step.

[0033] Constant current step

[0034] According to a first embodiment, the electrochemical nitridation process comprises at least one galvanostatic step.

[0035] During the constant current step, an anodic current representing a predetermined reference current density is applied between the substrate (which serves as an anode) and the counter electrode (which serves as a cathode) until a predetermined threshold voltage is reached, at which an iron nitride coating having a predetermined thickness is obtained. The anodic current applied during the constant current step may have a constant trend or a pulse trend; when the anodic current has a pulse trend, the average value of the anodic current represents the predetermined reference current density.

[0036] In other words, during the constant current step, an anodic current corresponding to a current density having a constant value or an average constant value is applied until a predetermined threshold voltage is reached and thus the desired thickness of the substrate surface coating portion is reached. In other words, during the constant current step, an anodic current having a constant value or an average constant value (constant average value) is applied.

[0037] The predetermined reference current density is to ensure that the nitrogen cations and / or nitrogen anions in the ionic liquid are at least partially decomposed to generate nitrogen species that can be used to form the nitride coating of the substrate.

[0038] Preferably, the predetermined reference current density has a value of at least 0.025 mA / cm 2 value, or at least 0.050mA / cm 2 value, or at least 0.075mA / cm 2 value, or at least 0.1mA / cm 2 value, or at least 0.2mA / cm 2 value, or at least 0.3mA / cm 2 value, or at least 0.4mA / cm 2 value, or at least 0.5mA / cm 2 value, or at least 0.6mA / cm 2 value, or at least 0.7mA / cm 2 value, or at least 0.8mA / cm 2 value, or at least 0.9mA / cm 2 value, or at least 1mA / cm 2 The value of .

[0039] Preferably, the predetermined reference current density has a value not exceeding 50 mA / cm 2 value, or not more than 45mA / cm 2 value, or not more than 40mA / cm 2 value, or not more than 35mA / cm 2 value, or not more than 30mA / cm 2 value, or not more than 25mA / cm 2 value, or not more than 20mA / cm2 value, or not more than 15mA / cm 2 value, or not more than 10mA / cm 2 value, or not more than 5mA / cm 2 The value of .

[0040] Preferably, the predetermined reference current density is between 0.5 mA / cm 2 With 50mA / cm 2 For example, the predetermined reference current density has a value between 0.5 mA / cm 2 With 20mA / cm 2 or the predetermined reference current density has a value between 0.5 mA / cm 2 With 10mA / cm 2 The value between .

[0041] The value of the reference current density varies depending on the resistance of the substrate to be coated, in particular, the value of the reference current density varies depending on how much native oxide is present on the surface of the substrate. This means that the thicker the native oxide layer covering the substrate (up to a few nanometers thick), and thus the greater the resistance of the substrate, the higher the reference current density value will be.

[0042] During the constant current step, the applied anode current may be either direct current or alternating current.

[0043] Preferably, the predetermined threshold voltage is at least 1V, or at least 2V, or at least 3V, or at least 4V, or at least 5V, or at least 6V, or at least 7V, or at least 8V, or at least 9V, or at least 10V.

[0044] Preferably, the predetermined threshold voltage is no more than 20V, or no more than 19V, or no more than 18V, or no more than 17V, or no more than 16V, or no more than 15V, or no more than 14V, or no more than 13V, or no more than 12V, or no more than 11V.

[0045] Preferably, the predetermined threshold voltage is between 1V and 20V, more preferably, the predetermined threshold voltage is between 1V and 12V, more preferably, the predetermined threshold voltage is between 1V and 10V, for example, the predetermined threshold voltage is 5V.

[0046] Preferably, when said threshold voltage is reached, an average coating thickness of at least 0.040 μm, preferably at least 0.1 μm, more preferably at least 1 μm, even more preferably between 1 μm and 5 μm is obtained.

[0047] The higher the threshold voltage, the faster the growth rate of iron nitride on the substrate, thereby forming a nitride coating. However, as the voltage increases, the gaseous products released from the electrolytic bath also increase. It has been found that a threshold voltage value between 1V and 20V ensures a good compromise between the coating growth rate and process efficiency.

[0048] The duration of the constant current step depends on the applied anodic current and the time required to reach the aforementioned predetermined threshold voltage.

[0049] As already mentioned, the thickness of the iron nitride coating obtained in the constant current step depends on the threshold voltage reached and therefore also on the time required to achieve this threshold voltage. In other words, the thickness of the iron nitride coating also depends on the duration of the constant current step.

[0050] Preferably, the constant current step has a duration of at least 5 minutes, or at least 10 minutes, or at least 15 minutes, or at least 20 minutes, or at least 25 minutes.

[0051] Preferably, the constant current step has a duration of no more than 180 minutes, or no more than 120 minutes, or no more than 60 minutes, or no more than 55 minutes, or no more than 50 minutes, or no more than 45 minutes, or no more than 40 minutes, or no more than 35 minutes, or no more than 30 minutes.

[0052] Preferably, the constant current step has a duration between 10 and 180 minutes, or the constant current step has a duration between 15 and 60 minutes, for example the constant current step has a duration of about 60 minutes.

[0053] Constant Potentiostatic Step

[0054] According to a second embodiment, the electrochemical nitridation process comprises at least one constant potential step.

[0055] During the constant potential step, a voltage having a value equal to a predetermined reference voltage is applied between the substrate (which serves as an anode) and the counter electrode (which serves as a cathode) until a threshold anodic current representing a predetermined threshold current density is reached, at which an iron nitride coating having a predetermined thickness is obtained. The voltage applied during the constant potential step may have a constant or pulsed tendency; when the voltage has a pulsed tendency, the average value of the voltage is equal to the predetermined reference voltage.

[0056] In other words, during the constant potential step, a constant voltage or an average constant voltage is applied until a threshold current density is reached and therefore the desired thickness of the substrate surface coating portion is reached. Therefore, the voltage applied during the constant current step has a constant value or an average constant value (constant average value).

[0057] Preferably, the threshold current density corresponds to a current density value below which the efficiency of the electrochemical process is low, since the thickness of the coating remains substantially constant in view of the gradual increase in power consumption.

[0058] The predetermined reference voltage is intended to generate an anode current that can at least partially decompose nitrogen cations and / or nitrogen anions in the ionic liquid, thereby generating nitrogen substances that can be used to form a nitride coating portion of the substrate; the predetermined reference voltage is also intended to overcome the resistance of the formed nitride coating portion.

[0059] Preferably, the predetermined reference voltage is at least 1V, or at least 2V, or at least 3V, or at least 4V, or at least 5V, or at least 6V, or at least 7V, or at least 8V, or at least 9V, or at least 10V.

[0060] Preferably, the reference voltage is no more than 50V, or no more than 45V, or no more than 40V, or no more than 35V, or no more than 30V, or no more than 25V, or no more than 20V, or no more than 15V.

[0061] Preferably, the predetermined reference voltage is between 1V and 20V, or between 1V and 10V, for example, the predetermined reference voltage is about 5V.

[0062] The value of the reference voltage varies according to the resistance of the substrate to be coated. This means that the greater the resistance of the substrate, the greater the value of the reference voltage so that the resistance of the nitride coating being formed can be overcome.

[0063] During the constant potential step, the applied voltage may be continuous or alternating.

[0064] Preferably, the predetermined threshold current density is at least 20 μA / cm 2 value, or at least 25μA / cm 2 value, or at least 30μA / cm 2 value, or at least 40μA / cm 2 value, or at least 45μA / cm 2 value, or at least 50μA / cm 2 The value of .

[0065] Preferably, the predetermined threshold current density is no more than 80 μA / cm 2 value, or not more than 75μA / cm 2 value, or not more than 70μA / cm 2 value, or not more than 65μA / cm 2value, or not more than 60μA / cm 2 value, or not more than 55μA / cm 2 The value of .

[0066] Preferably, the predetermined threshold current density is between 20 μA / cm 2 With 80μA / cm 2 More preferably, the predetermined threshold current density is between 30 μA / cm 2 With 70μA / cm 2 Even more preferably, the predetermined threshold current density is about 50 μA / cm 2 .

[0067] Preferably, when the threshold current density is reached, an average coating thickness of at least 0.040 μm, preferably an average coating thickness of at least 0.1 μm, more preferably an average coating thickness of at least 1 μm, even more preferably an average coating thickness between 1 μm and 5 μm is obtained.

[0068] The duration of the potentiostatic step depends on the applied voltage and the time required to reach the threshold anodic current.

[0069] As already mentioned, the thickness of the iron nitride coating obtained during the constant potential step depends on the threshold electrical density and therefore also on the time required to achieve this threshold electrical density. In other words, the thickness of the iron nitride coating also depends on the duration of the constant potential step.

[0070] Preferably, the constant potential step has a duration of at least 5 minutes, or a duration of at least 10 minutes, or a duration of at least 15 minutes, or a duration of at least 20 minutes, or a duration of at least 25 minutes.

[0071] Preferably, the constant potential step has a duration of no more than 180 minutes, or a duration of no more than 120 minutes, or a duration of no more than 60 minutes, or a duration of no more than 55 minutes, or a duration of no more than 50 minutes, or a duration of no more than 45 minutes, or a duration of no more than 40 minutes, or a duration of no more than 35 minutes, or a duration of no more than 30 minutes.

[0072] Preferably, the constant potential step has a duration between 15 and 180 minutes, or between 15 and 60 minutes, for example the constant potential step has a duration of about 60 minutes.

[0073] Galvanostatic step and potentiostatic step

[0074] According to a preferred embodiment, the electrochemical nitridation process comprises a constant current step and a constant potential step in sequence, wherein the constant potential step is after the constant current step. The two steps are as described above.

[0075] Preferably, the voltage applied during the potentiostatic step corresponds to the threshold voltage reached during the galvanostatic step.

[0076] Experiments have found that performing a constant current step first and then a constant potential step in sequence maximizes the efficiency of the electrochemical nitridation process in the following way: obtaining a coating having a desired average thickness, preferably an average thickness between 0.040 μm and 5 μm, more preferably an average thickness between 0.5 μm and 5 μm, and even more preferably an average thickness between 1 μm and 5 μm.

[0077] Without being bound by theory, during the constant current step, the nitrogen species generated by the decomposition of the nitrogen cations and / or nitrogen anions in the ionic liquid diffuse into the substrate in a controlled manner, thereby forming iron nitride. The resistance of the substrate increases with the formation of the nitride. During the constant potential step, the voltage is maintained at an average value equal to a predetermined value to allow the nitrogen species to diffuse effectively into the substrate.

[0078] Preferably, the electrochemical process comprising a constant current step and a constant potential step sequentially has a duration between 5 minutes and 180 minutes, more preferably, the electrochemical process comprising a constant current step and a constant potential step sequentially has a duration between 10 minutes and 120 minutes, more preferably, the electrochemical process comprising a constant current step and a constant potential step sequentially has a duration between 30 minutes and 60 minutes, for example, the electrochemical process comprising a constant current step and a constant potential step sequentially has a duration of about 60 minutes. The duration can vary depending on the temperature used for the electrochemical process.

[0079] The following description relates to an embodiment in which the electrochemical nitridation process includes only one constant current step, an embodiment in which the electrochemical nitridation process includes only one constant potential step, and an embodiment in which the electrochemical process includes sequentially one constant current step and one constant potential step.

[0080] As already mentioned above, the galvanostatic step and / or the potentiostatic step are performed with a constant trend of the anodic current and of the voltage, respectively, or with a pulsed trend of the anodic current and of the voltage, respectively.

[0081] In a preferred embodiment, the constant current step and / or the constant potential step are performed with a pulsed trend of the anodic current and a pulsed trend of the voltage, respectively. According to this embodiment, preferably, the amplitude of the pulses of the current and / or voltage is at least ±10% relative to the mean value; for smaller amplitudes, the pulsed trend will lead to an effect substantially the same as that of the constant trend. Preferably, each pulse of the current and / or voltage has a duration of at least 100 ms (milliseconds).

[0082] Advantageously, performing the galvanostatic step and / or the potentiostatic step in a pulsed manner allows limiting the possible formation of by-products on the substrate surface, reducing the release of gaseous by-products, and improving the local mixing of the ionic liquid, all of which contribute to improving the efficiency of the process.

[0083] According to a preferred embodiment, the electrochemical nitridation process of step b) of the method according to the invention is carried out under an inert atmosphere, for example under a nitrogen flow, thereby allowing to improve the efficiency of the nitridation process and reduce the occurrence of secondary reactions of iron oxide (e.g. rust) formation prior to nitridation.

[0084] According to a preferred embodiment, during the above-mentioned step a), the substrate is immersed in the electrolytic bath by means of a supporting structure (so-called support) which has the function of keeping the substrate immersed in the bath and simultaneously applying the current and / or voltage from the current generator and the voltage generator, respectively. In other words, the supporting structure advantageously ensures the electrical contact between the voltage generator / current generator and the substrate to be nitrided. Furthermore, the supporting structure advantageously allows the voltage and current applied to the substrate to be measured. Preferably, the supporting structure is made of metal, for example, the supporting structure is made of titanium or stainless steel.

[0085] According to an embodiment of the present invention, the non-aqueous electrolytic bath consists of the ionic liquid. According to this embodiment, no solvent is added to the electrolytic bath and the ionic liquid is used both as a reactant and as a solvent ("pure reaction").

[0086] According to an alternative embodiment, the non-aqueous electrolytic bath comprises the ionic liquid and a polar solvent, preferably, the polar solvent is an aprotic polar solvent. Preferably, the polar solvent is selected from acetonitrile, dimethylformamide, dimethyl sulfoxide, acetone. Adding a polar solvent to the electrolytic bath allows the viscosity of the ionic liquid to be adjusted, thereby increasing the conductivity of the ionic liquid and increasing the coulombic efficiency of the electrochemical process. This allows a nitride coating portion with greater thickness to be obtained.

[0087] Preferably, during the electrochemical process, the electrolytic bath is subjected to forced mixing, for example by means of a mixer and / or a stirrer, in order to increase the efficiency of the process.

[0088] As already mentioned, the ionic liquid comprises nitrogen cations and / or nitrogen anions.

[0089] Preferably, the nitrogen cation is selected from the group consisting of pyrrolidinium cations, imidazolium cations, morpholinium cations, piperidinium cations and ammonium cations. Preferably, the nitrogen cation is functionalized with an alkyl group, which is preferably selected from the group consisting of methyl, ethyl, propyl and butyl.

[0090] Preferably, the nitrogen anion is selected from the group consisting of dicyanamide anion, tricyanomethane anion, bis(trifluoromethylsulfonyl)imide anion, bis(fluorosulfonyl)imide anion, phosphate anion, hexafluorophosphate anion and nitrate anion.

[0091] According to a preferred embodiment, the ionic liquid includes a nitrogen cation and a nitrogen anion. Preferably, the ionic liquid is selected from: 1-propyl-1-methylpyrrolidine dicyanamide; 1-ethyl-1-methylpyrrolidine dicyanamide; 1-propyl-1-methylimidazol dicyanamide; 1-ethyl-1-methylimidazol dicyanamide; 1-ethyl-3-methylmorpholine dicyanamide; tributylmethylammonium bis(trifluoromethylsulfonyl)imide; butyltrimethylammonium bis(trifluoromethylsulfonyl)imide; choline bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazol bis(fluorosulfonyl)imide; 1-ethyl-3-methylimidazol bis(trifluoromethylsulfonyl)imide; 1-methyl-1-propylpiperidinium bis(trifluoromethylsulfonyl)imide; 1-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazol nitrate.

[0092] According to another embodiment, the ionic liquid comprises a nitrogen cation or a nitrogen anion. Preferably, the ionic liquid is selected from: tributylmethylphosphine bis(trifluoromethylsulfonyl)imide, diethylmethylsulfonium bis(trifluoromethylsulfonyl)imide, 1-methyl-1-propylpiperidinium tetrafluoroborate.

[0093] As already emphasized above, a substrate of iron or an iron alloy, for example cast iron or steel, is immersed as an electrode in an ionic liquid in the presence of a counter electrode, which serves as an anode and the counter electrode as a cathode.

[0094] Preferably, the counter electrode comprises a body made of graphite, or stainless steel, or titanium or aluminum. Advantageously, the material has a high electrical conductivity and at the same time does not decompose in the ionic liquid. More preferably, the counter electrode is graphite.

[0095] According to various embodiments, the counter electrode comprises a body immersed in the electrolytic bath, or the counter electrode comprises the same container immersed in the electrolytic bath as the substrate.

[0096] According to a preferred embodiment, the method of the invention comprises a step of pre-treating the substrate. Said pre-treatment step is performed upstream of step a) of immersing the substrate in the electrolytic bath.

[0097] Preferably, the pretreatment step comprises a "degreasing" step, in which any traces of grease and / or lubricant-coolant liquid are removed from the surface of the substrate. Preferably, during the "degreasing" step, the substrate is immersed in a polar solvent for a predetermined period of time, preferably for at least 30 seconds; optionally, during the "degreasing" step, the substrate is immersed in a polar solvent for a predetermined period of time, preferably for at least 30 seconds, with the application of ultrasound. The polar solvent is, for example, water, ethanol, or a mixture thereof; optionally, the water contains a surfactant. The substrate can then be rinsed with water and air-dried.

[0098] Preferably, the pretreatment step comprises a "surface treatment" step, in which any traces of oxides are removed from the surface of the substrate. Preferably, during the "surface treatment" step, the substrate is immersed in an acidic solution for a predetermined period of time, preferably for at least 1 minute, and then rinsed with water. The acidic solution is, for example, a 5% wt. hydrochloric acid aqueous solution.

[0099] Preferably, the pretreatment step comprises both the "degreasing" step and the "surface treatment" step.

[0100] After said pretreatment step, the substrate, which is respectively subjected to step a) of immersion in an electrolytic bath and step b) of an electrochemical nitridation process, advantageously presents an electrically conductive surface. Said pretreatment step is particularly preferred; in fact, if the surface of the substrate is contaminated with machining residues (for example lubricant-coolant liquid), islands of lower electrical conductivity may be formed on which the nitride coating will grow unevenly.

[0101] According to a preferred embodiment, the method of the invention comprises a step of post-treatment of the substrate. The post-treatment step is performed downstream of step b), ie downstream of the electrochemical nitridation process.

[0102] Preferably, the post-treatment step comprises a "rinsing" step, in which any ionic liquid residues are removed from the nitrided surface of the substrate. Preferably, during the "rinsing" step, the coated substrate is immersed in a polar solvent for a predetermined period of time, preferably the coated substrate is immersed in a polar solvent for at least 30 seconds. The polar solvent is, for example, water, ethanol, or a mixture thereof. The substrate may then be rinsed with distilled water. Preferably, the substrate is then air-dried.

[0103] Preferably, the post-treatment step also comprises a subsequent "heat treatment" step in order to improve the corrosion resistance of the substrate. During the "heat treatment" step, the substrate is heated to a temperature between 50°C and 200°C, for example between 50°C and 150°C, for a predetermined period of time, preferably for at least 30 seconds.

[0104] As already mentioned above, the object of the present invention is also an article comprising an iron or iron alloy (eg cast iron or steel) substrate and an iron nitride surface coating on said substrate, wherein said surface coating is obtainable by the above-described method.

[0105] Preferably, the surface coating comprises iron nitride Fe 2-3 A mixture of N and iron nitride Fe3N.

[0106] The articles of the invention are not limited to a particular geometry or morphology, since the method of the invention allows processing of any complex geometry that can be immersed in an electrolytic bath.

[0107] Preferably, the article is a component of a car or motorcycle, or a part of such a component.

[0108] In a particular embodiment, the object is a brake caliper of a braking system of an automobile or motorcycle, or a part of the brake caliper.

[0109] In another embodiment, the object is a brake disc of a braking system of a car or motorcycle, or is a part of the brake disc, for example, the object is a brake band.

[0110] Experimental Section

[0111] The cast iron sample was first immersed in an ultrasonic ethanol bath for more than 30 seconds, then immersed in an acid solution for more than 1 minute, and then rinsed with water.

[0112] The treated sample is mounted on a support structure (also called a holder, i.e., a metal rod on which the sample is hooked), and then immersed in an electrolytic bath comprising tributylmethylammonium bis(trifluoromethylsulfonyl)imide. A graphite counter electrode is also immersed in the electrolytic bath.

[0113] The sample was then subjected to an electrochemical process at room temperature comprising a first constant current step and a second constant potential step.

[0114] More specifically, a current with a current of 10 mA / cm2 was initially applied between the sample and the counter electrode. 2The anodic current was adjusted to an average current density of 50 μA / cm2 until a voltage of 5 V was reached; the first constant current step lasted about 10 minutes. Then, an average voltage of 5 V was applied between the sample and the counter electrode until a voltage of 50 μA / cm2 was measured. 2 The second constant current step lasts about 50 minutes.

[0115] After the electrochemical nitridation process was completed, the samples were immersed in an ethanol bath for more than 30 seconds. After immersion, the samples were rinsed with distilled water and allowed to air dry.

[0116] The sample thus obtained was coated with a uniform iron nitride layer having a thickness between about 0.5 μm and 1.0 μm. The layer also exhibited a low degree of crystallinity and a corrosion potential 78 mV higher than that of the uncoated sample, demonstrating that the sample coated using the method of the present invention has a higher corrosion resistance than the uncoated sample.

[0117] Figure 1 A comparison of the Raman spectrum of the coating obtained by the above method (Figure A) and the Raman spectrum of the coating obtained by the conventional ferrite nitrocarburizing process or FNC (Figure B) is shown. From the comparison of the two spectra, it can be seen that the coating obtained by the method of the present invention has a lower crystallinity and a different concentration of oxidation byproducts (e.g., Fe2O3, FeOOH). In a first approximation, the crystallinity can be evaluated by observing the width of the peak at the mid-height; the peak of the coating obtained by the method of the present invention shows a larger width at the mid-height compared to the coating obtained by the FNC technique.

[0118] Figure 2 Glow discharge optical emission spectroscopy (GD-OES) spectra obtained for a cast iron sample coated by the method of the present invention and the same cast iron sample without a coating are shown. Compared to the uncoated sample, the nitrided sample exhibits: 1) a nitrogen concentration peak just below the sample surface; and 2) a non-negligible nitrogen concentration away from the sample surface. This confirms that the coating obtained by the method of the present invention has been incorporated into the sample matrix.

[0119] Obviously, only one specific embodiment of the invention has been described. However, a person skilled in the art will be able to make all necessary modifications to the method for forming an iron nitride coating on the surface of an iron or iron alloy substrate in order to adapt the method to the specific conditions, without departing from the scope of protection as defined in the appended claims.

Claims

1. A method for forming an iron nitride coating portion on a surface of a substrate of iron or an iron alloy, the method comprising the following steps: a) immersing the substrate of iron or iron alloy in an electrolytic bath comprising an ionic liquid comprising nitrogen cations and / or nitrogen anions in the presence of a counter electrode acting as cathode, the substrate acting as anode; b) subjecting the substrate to an electrochemical nitridation process, wherein the electrochemical nitridation process comprises at least one of the following steps: - a constant current step in which an anodic current representing a predetermined reference current density is applied between the substrate and the counter electrode until a predetermined threshold voltage is reached at which an iron nitride coating having a predetermined thickness is produced on the substrate; - a constant potential step in which a voltage having a value equal to a predetermined reference voltage is applied between the substrate and the counter electrode until a threshold anodic current representing a predetermined threshold current density is reached, at which an iron nitride coating having a predetermined thickness is produced on the substrate.

2. The method according to claim 1, wherein: The ionic liquid is at a temperature below 250°C, preferably, the ionic liquid is at a temperature below 200°C, more preferably, the ionic liquid is at room temperature.

3. The method according to claim 1 or 2, wherein: The electrochemical nitridation process according to step b) is carried out at a temperature below 250°C, preferably, at a temperature below 200°C, and more preferably, at room temperature.

4. A method according to any one of the preceding claims, wherein: The step b) includes the constant current step and the constant potential step in sequence, and the constant potential step is after the constant current step.

5. A method according to any one of the preceding claims, wherein: During the constant current step, the anode current has a constant trend.

6. The method according to any one of claims 1 to 4, wherein: During the constant current step, the anode current has a pulse trend, and the average value of the anode current represents the predetermined reference current density.

7. A method according to any one of the preceding claims, wherein: During the constant potential step, the voltage has a constant trend.

8. The method according to any one of the preceding claims 1 to 7, wherein: During the constant potential step, the voltage has a pulse trend, and the average value of the voltage is equal to the predetermined reference voltage.

9. A method according to any one of the preceding claims, wherein: The predetermined reference current density is between 0.5 mA / cm 2 With 50mA / cm 2 Preferably, the predetermined reference current density has a value between 0.5 mA / cm 2 With 20mA / cm 2 or the predetermined reference current density has a value between 0.5 mA / cm 2 With 10mA / cm 2 The value between .

10. The method according to any one of the preceding claims, wherein: The predetermined threshold voltage is between 1V and 20V, preferably, the predetermined threshold voltage is between 1V and 12V, and more preferably, the predetermined threshold voltage is between 1V and 10V.

11. A method according to any one of the preceding claims, wherein: The predetermined reference voltage is between 1V and 50V, preferably, the predetermined reference voltage is between 1V and 20V, and more preferably, the predetermined reference voltage is between 1V and 10V.

12. A method according to any one of the preceding claims, wherein: The predetermined threshold current density is between 20 μA / cm 2 With 80μA / cm 2 Preferably, the predetermined threshold current density is between 30 μA / cm 2 With 70μA / cm 2 More preferably, the predetermined threshold current density is about 50 μA / cm 2 .

13. A method according to any one of the preceding claims, wherein: The electrochemical nitridation process according to step b) has a duration between 5 minutes and 180 minutes, preferably, the electrochemical nitridation process according to step b) has a duration between 10 minutes and 120 minutes, and more preferably, the electrochemical nitridation process according to step b) has a duration between 30 minutes and 60 minutes.

14. The method according to any of the preceding claims, forming an iron nitride coating having an average thickness between 0.040 μm and 5 μm, preferably forming an iron nitride coating having an average thickness between 0.5 μm and 5 μm, more preferably forming an iron nitride coating having an average thickness between 1 μm and 5 μm.

15. A method according to any one of the preceding claims, wherein: The ionic liquid is a room temperature ionic liquid (RTIL).

16. A method according to any one of the preceding claims, wherein: The ionic liquid comprises: A nitrogen cation selected from the group consisting of a pyrrolidinium cation, an imidazolium cation, a morpholinium cation, a piperidinium cation and an ammonium cation, preferably the cation is functionalized with an alkyl group, preferably selected from the group consisting of methyl, ethyl, propyl and butyl, and / or The nitrogen anion is selected from the group consisting of a dicyanamide anion, a tricyanomethane anion, a bis(trifluoromethylsulfonyl)imide anion and a bis(fluorosulfonyl)imide anion, a phosphate anion, a hexafluorophosphate anion and a nitrate anion.

17. A method according to any one of the preceding claims, wherein: The ionic liquid comprises nitrogen cations and nitrogen anions. Preferably, the ionic liquid is selected from: 1-propyl-1-methylpyrrolidine dicyanamide; 1-ethyl-1-methylpyrrolidine dicyanamide; 1-propyl-1-methylimidazole dicyanamide; 1-Ethyl-1-methylimidazole dicyanamide; 1-Ethyl-3-methylmorpholine dicyanamide; Tributylmethylammonium bis(trifluoromethylsulfonyl)imide; Butyltrimethylammonium bis(trifluoromethylsulfonyl)imide; Choline bis(trifluoromethylsulfonyl)imide; 1-Ethyl-3-methylimidazole bis(fluorosulfonyl)imide; 1-Ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide; 1-Methyl-1-propylpiperidinium bis(trifluoromethylsulfonyl)imide; 1-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazole nitrate.

18. The method according to any one of claims 1 to 16, wherein: The ionic liquid is tributylmethylphosphine bis(trifluoromethylsulfonyl)imide, diethylmethylsulfonium bis(trifluoromethylsulfonyl)imide, or 1-methyl-1-propylpiperidinium tetrafluoroborate.

19. A method according to any one of the preceding claims, wherein: During step a), the substrate is immersed in the electrolytic bath via a supporting structure, a so-called rack.

20. A method according to any one of the preceding claims, wherein: The counter electrode includes a body made of graphite, or stainless steel, or titanium, or aluminum.

21. A method according to any one of the preceding claims, wherein: The counter electrode comprises a body immersed in the electrolytic bath, or the counter electrode comprises a container of the electrolytic bath.

22. The method according to any one of the preceding claims, comprising a pretreatment step of pretreating the substrate upstream of step a), the pretreatment step in turn comprising: a "degreasing" step, in which the substrate is immersed in a polar solvent for a predetermined period of time, preferably for at least 30 seconds; optionally, the substrate is immersed in a polar solvent for a predetermined period of time, preferably for at least 30 seconds, under the application of ultrasound, and / or A "surface treatment" step, in which the substrate is immersed in an acidic solution for a predetermined period of time, preferably, the substrate is immersed in an acidic solution for at least 1 minute, and then the substrate is rinsed with water.

23. The method according to any of the preceding claims, comprising a post-treatment step of post-treating the substrate downstream of step b), in which the substrate is immersed in a polar solvent for a predetermined period of time, preferably for at least 30 seconds, and optionally, the substrate is heated to a temperature between 50°C and 200°C for a predetermined period of time, preferably for at least 30 seconds.

24. An article comprising a substrate of iron or an iron alloy and comprising an iron nitride surface coating on the substrate, wherein: The surface coating can be obtained by a method according to any of the preceding claims.

25. The article of claim 24, wherein: The surface coating portion includes iron nitride Fe 2-3 A mixture of N and iron nitride Fe3N.

26. The article according to claim 24 or 25, which is a brake caliper or a brake disc of a braking system of an automobile or a motorcycle, or which is a part of the brake caliper or the brake disc.